Flecainide induced wide QRS Tachycardia - Gjoko Spasevski; Elena Kikirkovska; Antonio Georgiev (MIT Univerzitet Skopje, 2021)
In this case report we present a 54-year-old patient hospitalized in the rhythmology department, who complains of fatigue and shortness of breath. The electrocardiogram showed atrial flatter with a frequency of 140 / min. After treatment with flecainide, the patient is converted to a sinus rhythm with a frequency of 75 / min. A coronary load stress test was then performed, in which in the recovery phase, the patient switched from a sinus rhythm to a wide QRS atrial flutter with a 1:1 conduction. Echocardiography subsequently revealed dilated left ventricle with global hypokinesia and an ejection fraction of 41%.